Piping databook - Nayyar, Mohinder L. (McGraw-Hill / Irwin, 2002)
Stay on top of piping details and procedures with the help of this desk-top handbook - covers all types of pipes and piping uses. Access scores of illustrations for metallic, non-metallic, and lined piping. Includes many specification tables and standards.